Specifics of the Energy Markets - Delia Vasilica Rotaru (CES Working Papers, 2014)
In this paper we have analyzed the specific characteristics of the energy markets in general and the products transacted, in particular. Due to its unique features, electricity, one of the most important products for the economic development of a country, has brought challenges to the organization of a liberalized market to be transacted on. The paper also offers a view on the evolution of the supply and demand on the energy market in the last past years, along with a forecast analysis. The last part of the paper offers a presentation of the specific steps taken in the deregulation of the energy market process.
Keywords: L51; Q48; 330; energy market; electricity; oil; gas; coal; supply; demand